Anticipation performance in virtual reality boxing: impact of gaze-contingent blur on elite boxers - Limballe, A.; Kulpa, R.; Verhulst, E.; Ledouit, S.; Bennett, S. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Perceptual-motor skills are essential to performance in combat sports but remain poorly trained (Romeas et al., 2022), often with a focus on reaction time. Therefore, we studied how the properties of VR (standardization, reproducibility, and perception-action coupling) can facilitate the development of new tools that assess perceptual-motor skills underlying performance. Particularly, we are interested in the impact of a visual blur on anticipation in boxing. The introduction of blur inhibits visual perception of fine details that can act as distractors but preserves essential information such as the kinematics of the opponents limbs. To date, blur has been applied in real word settings using lenses (Mann et al. 2010) or 2D computer blurred displays (Ryu et al. 2015). Using 2D video display and gaze-contingent blur, Ryu et al. reported that novices, but not experts, decision making benefited when a moderate level of blur was applied in peripheral vision. However, these studies did not manipulate the location of blur in a realistic 3D visual task, where normal perception-action coupling was preserved.